A low mutual coupling antenna array using alternating-direction S-shaped defected ground structures - Tianqi Jiao; Tao Jiang; Yingsong Li (2016 IEEE 5th Asia-Pacific Conference on Antennas and Propagation (APCAP), 2016)
A two-element low mutual coupling antenna array is designed by using alternating-direction S-shaped defected ground structures (ADS-DGSs). The proposed antenna array operates at 2.45GHz WLAN band, and it consists of two identical rectangle patch antennas and a pair of ADS-DGSs etching on the common ground plane. The performance of the proposed antenna is numerically investigated in order to achieve a high isolation. The mutual coupling of the antenna array is reduced by means of the ADS-SGS. Simulated results show that the design can provide a 30 dB mutual coupling reduction at the operating band.